KELAS SOSIAL DALAM NOVEL BUKAN PASAR MALAM KARYA PRAMOEDYA ANANTATOER - Sopia Erni; Yasnur Asri; Nurizzati Nurizzati (Jurnal Bahasa dan Sastra, 2012)
This research aims to describe (1) the social class in the Bukan Pasar Malam Pramoedya Ananta Toer novel, (2) conflict of social class in the Bukan Pasar Malam Pramoedya Ananta Toer novel, (3) the impact conflict of social class in the novel of Bukan Pasar Malam Pramoedya Ananta Toer. The theory used to achieve the goal: the sociology of literature, in particular the theory of social classes and conflict of social class. This research is descriptive qualitative research method with content analysis techniques. The data of this study are quoted or written words of the object to be observed that leads to social class. Sources of data in this study is Bukan Pasar Malam Pramoedya Ananta Toer novel issued by the Balai Pustaka in 1959. Social class in the novel of Night Market Pramoedya Ananta Toer are: 1) an overview of social class, upper class earn a decent living with luxurious amenities, while the lower class they are very difficult to get some foods, 2) social class conflict, causing rebellion within the lower social class as it gets unfair treatment by the upper classes, 3) the impact of conflict of social class produce impact to deficity and suffering to the lower classes, such as the family, education and healthy.